Development and Validation of Teneligliptin Stereoisomers by HPLC Using Cellulose Based Immobilized Polysaccharide Chiral Stationary Phase - Gunnam, Srinivasu; Choppari, Thirupathi; Lakshmi, Narayana C.; Cherla, Parameswara Murthy; Siddiqui, Sarah Imam (Current Pharmaceutical Analysis, 2021)
Background: There is no single chiral method for the quantitation of teneligliptin stereoisomers by high performance liquid chromatography (HPLC). Hence, there is a need for the quantification of teneligliptin (TNGP) and its stereoisomers. Objective: The main aim of the research work is to develop a novel simple, selective, precise and accurate HPLC method for the separation of TNGP and its stereoisomers. Methods: Different screening trials were executed by changing the mobile phase compositions to normal phase and polar mode and also by utilizing the different immobilized polysaccharide chiral columns like CHIRALPAK IA, IC, ID, IE, IF and IG. All the stereoisomers were eluted with high resolution, on CHIRALPAK IC-3 (4.6×250 mm), 3 μm chiral stationary phase (CSP) with a flow rate of 0.7 mL/min. The chromatographic system was processed with isocratic mode comprising ethanol: acetonitrile: ethanolamine in the proportion of 90:10:0.1% v/v/v with a column oven temperature of 15°C and detection wavelength of 250 nm. Results: The limit of detection (LOD) and limit of quantification (LOQ) values of TNGP(API), R,S-isomer, S,R-isomer and R,R-isomer were found to be 0.036/0.11, 0.029/0.09, 0.038/0.011 and 0.020/0.06 μg/mL, respectively. The method was found to be precise, accurate and linear (R2 > 0.999). Conclusion: The developed method was successfully applied for the quantification of bulk drug without any interference with the extraneous components. Hence, the method can be utilized successfully in the pharmaceutical organizations for the separation and quantification of TNGP isomers.
Keywords: CHIRALPAK IC-3